Evaluation of psychological stress, cortisol awakening response, and heart rate variability in patients with chronic prostatitis/chronic pelvic pain syndrome complicated by lower urinary tract symptoms and erectile dysfunction - Bai, Jian; Gu, Longjie; Chen, Yinwei; Liu, Xiaming; Yang, Jun; Li, Mingchao; Dong, Xiyuan; Yang, Shulin; Huang, Bo; Wang, Tao; Jin, Lei; Liu, Jihong; et al. (Frontiers in Psychology, 2022)
Background Mental stress and imbalance of its two neural stress systems, the autonomic nervous system (ANS) and the hypothalamic–pituitary–adrenal (HPA) axis, are associated with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and erectile dysfunction (ED). However, the comprehensive analyses of psychological stress and stress systems are under-investigated, particularly in CP/CPPS patients complicated by lower urinary tract symptoms (LUTS) and ED. Materials and methods Participants were 95 patients in CP/CPPS+ED group, 290 patients in CP/CPPS group, 124 patients in ED group and 52 healthy men in control group. The National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), the International Index of Erectile Function-5 (IIEF-5) and the International Prostate Symptom Score (IPSS) were used for assessing the disease severity of CP/CPPS, LUTS and ED. Psychometric self-report questionnaires including the Beck Anxiety Inventory (BAI), Perceived Stress Scale (PSS), Type A Personality Test (TAPT) and Symptom Checklist 90 (SCL-90) were completed for distress from physical symptoms. Twenty-five subjects per group were randomly selected for further investigating the changes of the HPA axis and ANS. Saliva samples were taken on 3 consecutive days at 8 specific times with strict reference to time of morning awakening for evaluation of free cortisol. Heart rate variability (HRV) as marker of the ANS was measured using 24 h electrocardiography, and time-and frequency-domain variables were analyzed. Results The BAI and SCL-90 scores were significantly higher in the CP/CPPS+ED, CP/CPPS and ED groups compared with the control group (p < 0.01). The PSS scores of both groups with ED were significantly higher than the control group (p < 0.01). Compared with the CP/CPPS group, the differences of PSS, SCL-90 and TAPT scores were statistically significant in CP/CPPS+ED patients (p < 0.01). The IPSS scores were shown to have significantly positive correlations with BAI (r = 0.32, p < 0.0001), PSS (r = 0.18, p < 0.01) and SCL-90 (r = 0.19, p < 0.01) in the CP/CPPS patients. However, in all subjects, the IIEF-5 scores were shown to have significantly negative correlations with BAI (r = −0.17，p < 0.001), PSS (r = −0.25，p < 0.0001), SCL-90 (r = −0.20，p < 0.001) and quality of life score in NIH-CPSI (r = −0.14，p = 0.0075). Cortisol awakening response (CAR) parameters and diurnal cortisol levels did not significantly vary between the four groups. Time-dependent parameters of HRV also did not differ significantly across groups. In the frequency domain analysis, low frequency (LF) was significantly lower in ED patients when compared with CP/CPPS+ED patients (p = 0.044) and healthy controls (p = 0.005), high frequency (HF) power was significantly higher in healthy controls compared to patients with ED (p < 0.001), CP/CPPS (p < 0.001) and CP/CPPS+ED (p < 0.001), and the CP/CPPS+ED group had significantly higher LF/HF ratio than the control group (p = 0.001). Conclusion CP/CPPS and ED patients score exceedingly high on most psychosocial variables. The symptom scores of LUTS and ED positively correlate with the severity of psychological stress. Our findings also suggest that the ANS sympathovagal imbalance is associated with ED and LUTS in CP/CPPS, whereas HPA axis activity is not.